1980
DOI: 10.1128/aac.17.3.322
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sulfamethoxazole and trimethoprim on human neutrophil and lymphocyte functions in vitro: in vivo effects of co-trimoxazole

Abstract: Tetrazolium reduction, glycolysis, hexose monophosphate shunt activity, myeloperoxidase-mediated protein iodination, hydrogen peroxide production, and degranulation were assessed. The effects on lymphocyte mitogen-induced transformation were also evaluated. It was found that the test agents individually and in combination at high concentrations (>100 ,ig/ml) caused the inhibition of neutrophil postphagocytic myeloperoxidase-mediated protein iodination, which was related to the interference with H202 formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…In our study, the direct assessment of PMNL microbicidal function was measured by the ability of PMNLs to phagocytose and kill yeast cells. Even though no interference with phagocytosis was observed with cephalothin or trimethoprim, in agreement with previous work (3,11), or with tetracycline, inhibition of killing was demonstrated at therapeutic concentrations with cephalothin (20 ug/ml), tetracycline (5,ug/ml), and trimethoprim (5 jig/ml).…”
Section: Methodssupporting
confidence: 75%
“…In our study, the direct assessment of PMNL microbicidal function was measured by the ability of PMNLs to phagocytose and kill yeast cells. Even though no interference with phagocytosis was observed with cephalothin or trimethoprim, in agreement with previous work (3,11), or with tetracycline, inhibition of killing was demonstrated at therapeutic concentrations with cephalothin (20 ug/ml), tetracycline (5,ug/ml), and trimethoprim (5 jig/ml).…”
Section: Methodssupporting
confidence: 75%
“…In humans, trimethoprim administered in combination with another sulphonamide, sulphamethoxazole, in the ratio 1:5, caused a dosedependent depression of PHA-induced blastogenesis at a concentration of 1 g:5 g ml 1 (Gaylarde & Sarkany, 1978). In other studies (Anderson et al, 1980;Banck & Forsgren, 1979) no e#ect on the blastogenesis was observed except when tested at concentrations higher than those clinically obtainable (>100 g ml 1 ). Anderson et al (1980) studied lymphocytes from three healthy volunteers who received the combination tablets, administered orally twice a day (80 mg trimethoprim/400 mg sulphamethoxazole) over a 5 day period.…”
Section: T Lundén and G Bylundmentioning
confidence: 86%
“…Whatis the possible site of action of S/T? In 1980, Anderson et al reported that a high concentration of S/T inhibits postphagocytic H2O2production by neutrophils in vitro (25), and thus S/T may have a direct influence on neutrophil function. However, the sameauthors also reported that administration of four ST tablets daily to healthy volunteers did not alter neutrophil function in vivo.…”
Section: Discussionmentioning
confidence: 99%